Evaluation Of An Antimicrobial Stewardship Program Implementation For Surgical Prophylaxis In A Referral Hospital In The Kingdom Of Saudi Arabia - Ahmad, Nehad Jaser Yousef (2023)
Antimicrobial stewardship refers to the coordinated efforts to enhance the use of antimicrobial agents by encouraging the use of proper antibiotic selection, method of administration, antimicrobial dose, and duration of therapy. The current study sought to determine the efficacy of antimicrobial stewardship measures in improving antibiotic use in surgical patients.